Les pronoms clitiques du francoprovençal: l’étude du dialecte de Pélussin - Horváth, Márton Gergely (Verbum – Analecta Neolatina, 2008)
The status of clitic or conjunctive pronouns of Romance languages is a highly debated topic in linguistic literature. A number of articles dedicated to this issue propose to analyse clitic pronouns as affixes that have lost their syntactic autonomy, whereas others assert that they are syntactically accessible arguments of the verb. This article focuses on the exposition and study of clitic pronouns in the francoprovençal dialect of Pélussin from the perspective of their syntactic and morphosyntactic properties. We conduct a survey of the criteria usually employed to distinguish between affixes and clitics, in order to attempt to determine how the clitic pronouns of this patois should be analysed. We conclude that the dialect of Pélussin is very similar to colloquial French from this point of view, hence it follows that the analyses put forward previously for the latter also apply to the dialect presented herein.